Transformation properties of type 5 adenovirus mutants that differentially express the E1A gene products. - Haley, K P (1984)
Type 5 adenovirus mutants that differentially express E1A 13S, 12S, or 9S mRNAs were constructed to study the role of their gene products in transformation. H5dl520 expresses the 243-amino-acid (AA) protein encoded in the 12S mRNA but not the 13S mRNA-encoded 289-AA protein. This mutant transformed both cloned rat embryo fibroblast (CREF) cells and baby rat kidney (BRK) cells at a frequency 40-100 times greater than did wild-type viruses. In addition, all of the foci produced were fibroblastic and grew very slowly at 32 degrees C. In contrast, H5dl21, which was mutated so that only the 54-AA protein encoded by the 9S mRNA was synthesized, did not transform either cell type. DNA transfection studies with plasmids from which these mutants were constructed demonstrated that the differences in transformation frequencies were not as marked. The plasmid pD1/D2, which directs the synthesis of the 54-AA protein only, was found to transform baby rat kidney cells at low frequency, provided the gene was linked to a fragment from the simian virus 40 genome containing the transcriptional enhancer element.